Compensation of the effects of humidity on dielectric strength of air insulation - Mahant, Nilanshu (My University, 2023)
Abstract The effect of atmospheric conditions on the dielectric strength of air insulation is a complex issue that has been studied extensively around the world for many years. Although a lot of data is available, we are still a long way from full understanding of the impact of meteorological circumstances on the performance of air insulation. The purpose of this master’s thesis is to investigate and to develop a new strategy for rectification of the atmospheric condition correction method suggested in the IEC60060 standard. The current IEC technique leads to uncertainties in evaluations of withstand test results, in particular, significant deviations of insulation breakdown voltages at lower humidity conditions compared with standard atmospheric conditions. In order to account for the impact of low humidity on air insulation, data from earlier studies have been used. The effectiveness of environmental parameters has been studied using machine learning tools and regression analysis. As the result, equations for calculating the humidity correction factor are suggested. It is shown that the proposed method provides more accurate estimations compared with the standard correction procedure.
Keywords: HVDC, Insulation, Atmospheric condition, Low humidity, Air insulation, Rod-plane, Toroid-plane, Sphere-plane